Parameter Study and Economic Efficiency Optimization for Laser Cladding with Wide-Band Fiber Laser - Hu, Bin; Han, Jianhai; Wang, Junhua (International Journal of Optics, 2022)
With the aim of investigating the cladding geometry characteristics by a wide-band fiber laser with coaxial rectangular nozzle, and optimizing the powder efficiency and deposition speed for economy efficiency, Fe-based alloy powder was deposited on AISI 1045 substrate by a 3000 W fiber laser in this study. Laser power (P), scan speed (V), and powder feed rate (F) were selected for a factorial design. The effects of the three process parameters on the geometry characteristics and economic efficiency of single tracks were statistically analyzed, and a linear regression model was established between the combined parameters and the relevant characteristics (including track height, ratio of track width to height, powder efficiency, and deposition speed). A process map was developed with the track shape and key economic indexes as boundaries. A flat-top feature of the track profile was found and can be utilized to achieve good cladding evenness. The process map showed that the powder efficiency and deposition speed were higher than 50% and 20 mm3/s, respectively, when selecting process parameters in the as-built operation window.